Long-term Profitability Analysis of Commercial Banks in Nepal - Shrestha, Bijaya Prakash (PYC Nepal Journal of Management, 2011)
With the growing number of commercial banks in the country, a question as to whether they remain profitable in the long-term has become relevant. To address the question, the article has sampled 7 commercial banks established in and before 1995 and having positive net-worth growth for the period between 2003/04 and 2009/10. Considering the net-worth of commercial banks as the long-term investment, the study has examined their profitability in terms of various financial tools and indicators to conclude that they are likely to be financially sound and viable in the next 5 years also.